Label-free, high-throughput assay of human dendritic cells from whole-blood samples with microfluidic inertial separation suitable for resource-limited manufacturing - Caffiyar, M.Y. (MDPI AG, 2020)
Microfluidics technology has not impacted the delivery and accessibility of point-of-care health services, like diagnosing infectious disease, monitoring health or delivering interventions. Most microfluidics prototypes in academic research are not easy to scale-up with industrial-scale fabrication techniques and cannot be operated without complex manipulations of supporting equipment and additives, such as labels or reagents. We propose a label-and reagent-free inertial spiral microfluidic device to separate red blood, white blood and dendritic cells from blood fluid, for applications in health monitoring and immunotherapy. We demonstrate that using larger channel widths, in the range of 200 to 600 Î¼m, allows separation of cells into multiple focused streams, according to different size ranges, and we utilize a novel technique to collect the closely separated focused cell streams, without constricting the channel. Our contribution is a method to adapt spiral inertial microfluidic designs to separate more than two cell types in the same device, which is robust against clogging, simple to operate and suitable for fabrication and deployment in resource-limited populations. When tested on actual human blood cells, 77 of dendritic cells were separated and 80 of cells remained viable after our assay. Â© 2020 by the authors.